ETOS KERJA TUTOR KABUPATEN HULU SUNGAI TENGAH - Siti Aisyah (Universitas Lambung Mangkurat, 2013)
This study aims to determine the work spirit of lecture in Hulu Sungai Tengah. This study includes a quantitative descriptive research. Quantitative descriptive approach involves collecting data to answer several research questions related to the status of the study subjects were examined and denoted by using numbers. The data examined in this study is a tutor at Hulu Sungai Tengah, amounting to 30 tutors. Based on this research, work spirit of lecture in Hulu Sungai Tengah. In generally fall into either category, it can be evidenced by ownership category of each aspect. This is supported by advanced data, which is an average score for each aspect of the data is higher than the average edial. Most aspects contribute to the formation of tutors work spirit is a commitment (93%) and interest (70%) who claimed to have a high commitment and interest. Aspects of motivation is the most minor aspect in the formation work spirit of lectures in Hulu Sungai Tengah that only 37% had high motivation.Key words: Work spirit, and lecture